Uma contribuição ao estudo do planejamento temporal em inteligência artificial - Costa, Malgarete Rodrigues da (2005)
In this work it is studied the main methods of temporal planning. It is proposed solutions based on graph of plans as well as solutions based on the translation of graph of plans into time Petri nets. A review is presented about the algorithms for the treatment of classical planning and temporal planning. This review aims at to present the context of this work. Subsequently, it is proposed a new method of temporal treatment for the graph of plans and its translation into a time Petri net.